2008
DOI: 10.1007/s00108-008-2092-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronische Nierenerkrankungen und kardiovaskuläres System

Abstract: Depending on the reduction in glomerular filtration rate (GFR) as a measure of renal insufficiency and depending on their age, patients with chronic kidney disease have a 1.5 to 1,000-fold higher cardiovascular risk. Renal insufficiency is inherently an independent risk factor for cardiovascular events, which is likewise the case for patients also presenting with hypertension or diabetes mellitus. When cardiac insufficiency or coronary heart disease is already manifest, the GFR is the most important predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…90 mL/min/1.73 m 2 , and showed that AIP can not only predict CVD morbidity but also predict the development of renal dysfunction, which added to evidence indicating that CVD and CKD may have a similar pathophysiology. In fact, both the processes share certain pathophysiological mechanisms, such as endothelial dysfunction, increased oxidative stress, vascular ossification, and inflammation [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…90 mL/min/1.73 m 2 , and showed that AIP can not only predict CVD morbidity but also predict the development of renal dysfunction, which added to evidence indicating that CVD and CKD may have a similar pathophysiology. In fact, both the processes share certain pathophysiological mechanisms, such as endothelial dysfunction, increased oxidative stress, vascular ossification, and inflammation [43][44][45].…”
Section: Discussionmentioning
confidence: 99%